Intraoperative Blood Loss Reduction During Caesarean Delivery- Rectal Misoprostol Versus Oxytocin Infusion- A Randomized Controlled Trial - Ozori, Ebiogbo S.; Isa, Ibrahim A.; Nuvie, Oyeyemi; Oweisi, Peter W.; Zakaa, Zawua; Ochuko, Alabintei M.; Okpara, Abuchi L.; Ogidigba, Peter I. (British Journal of Healthcare and Medical Research, 2022)
The first drug of choice recommended by the World Health Organization (WHO) for the prevention of primary postpartum haemorrhage during caesarean section is oxytocin. However, when oxytocin’s efficacy is questionable due to poor transportation, suboptimal storage and or adulteration as seen in developing countries, an adjunctive, synergistic and cheaper as well as temperature-stable, uterotonic such as misoprostol would be needed. The study was aimed at comparing the effectiveness of rectal misoprostol with that of oxytocin infusion in intraoperative blood loss reduction during caesarean section. The trial involved one hundred and forty pregnant women who had unequivocal indications for caesarean section and had risk factors for primary postpartum haemorrhage were randomized equally into two study groups, after informed consent. One study arm received adjunctive 40 IU of oxytocin infusion and the other arm received adjunctive 600 ug of rectally administered misoprostol, after clamping of the edges of the uterine wound with Green-Armytage forceps at caesarean section. The primary outcome measure was intraoperative blood during caesarean section. The statistical significance was set at p-value of 0.05. There was no statistically significant difference between the study groups in reduction of intraoperative blood loss during caesarean section (603.5 ± 153.8 ml vs 597.4 ± 200.9 ml, p= 0.839). It was concluded that rectally administered 600 ug misoprostol is an effective, non-inferior adjunctive uterotonic comparable to 40 IU oxytocin infusion in reducing intraoperative blood loss during caesarean section.